Analisis Strategi Komunikasi Kebijakan Penggunaan Gadget/Handphone dalam Proses Pembelajaran (Studi Kasus PAUD Bunga Cempaka) - Putri Anggreani; Priatna (An Nafi': Multidisciplinary Science, 2025)
This study aims to analyze the communication strategy of gadget use policy in the learning process at PAUD Bunga Cempaka. In today's digital era, gadgets are not only entertainment tools but also learning media for early childhood. However, without an effective communication strategy, gadget use may negatively affect children's social and emotional development. This research uses a qualitative approach through in-depth interviews with the school principal and students’ parents. The results show that PAUD Bunga Cempaka implements a communication strategy involving information dissemination via meetings and WhatsApp groups, education on the positive and negative impacts of gadgets, and open discussion opportunities for parents. Gadget usage is limited to specific times and tailored to educational content. This strategy helps raise parental awareness in accompanying their children and balancing technology with communication development. The study contributes to formulating child-friendly educational policies that embrace technology while prioritizing healthy development.